2006
DOI: 10.1159/000093242
|View full text |Cite
|
Sign up to set email alerts
|

A Longitudinal Study of Health-Related Quality of Life of First Stroke Survivors’ Close Relatives

Abstract: Background and Purpose:Mental and social burdens of stroke patients’ relatives have been investigated repeatedly, but there is little information about their quality of life (QoL). The purpose of the study was to describe the health-related QoL of stroke patients’ relatives at 3 points in time after the stroke. Method: Sixty-four closest relatives of patients suffering from a disabling stroke were questioned at admission to inpatient rehabilitation as well as 6 months and 1 year after discharge with the SF36 (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
23
1
7

Year Published

2007
2007
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 28 publications
(31 citation statements)
references
References 61 publications
0
23
1
7
Order By: Relevance
“…2 In these stages, the patients' future disability is uncertain, and uncertainty and anxiety are powerful stressors. 1,9 The patients' depressive symptoms usually decrease over time. 2 However, as has also been found by others, 4,11 our results suggest that spouses' depressive symptoms take a different course.…”
Section: Course Of Psychosocial Functioningmentioning
confidence: 99%
See 1 more Smart Citation
“…2 In these stages, the patients' future disability is uncertain, and uncertainty and anxiety are powerful stressors. 1,9 The patients' depressive symptoms usually decrease over time. 2 However, as has also been found by others, 4,11 our results suggest that spouses' depressive symptoms take a different course.…”
Section: Course Of Psychosocial Functioningmentioning
confidence: 99%
“…Whereas some of these studies found a decrease in caregiver burden and depression over the first year after stroke, 1,4,5 others found stable stress levels 6 -8 or deterioration of caregiver quality of life between 6 months after discharge from inpatient rehabilitation and 1 year poststroke. 9 Although a chronic stressor may also have a delayed effect on quality of life, few studies 2,10 -12 have addressed changes in the caregiving experience beyond the first year after stroke. These studies found little change over time in burden, depressive symptoms, and quality of life.…”
mentioning
confidence: 99%
“…Changes have been reported over the post-stroke course in the perceived health-related quality of life of carers [18] suggesting that carers go through different stages while coping with the chronic illness of their family members [19]. This may explain why the reduced caregivers' QOL reported in the immediate post-stroke period [20] may be sustained at 3 months [5] or may improve or reduced within two years depending on the degree of disability and the presence or absence of communicative problems in the stroke survivor [14,21].…”
Section: Introductionmentioning
confidence: 99%
“…There is growing awareness of the negative physical and emotional consequences of providing informal, unpaid care for survivors of stroke [1,2,3,4]. Informal carers are usually family members (spouse, partner or child) who are often propelled into the caring role due to the sudden and unexpected nature of stroke and family obligation.…”
Section: Introductionmentioning
confidence: 99%